Carcinogenic mechanisms of virus-associated lymphoma - Zhang, Ying; Guo, Wei; Zhan, Zhumei; Bai, Ou (Frontiers in Immunology, 2024)
The development of lymphoma is a complex multistep process that integrates numerous experimental findings and clinical data that have not yet yielded a definitive explanation. Studies of oncogenic viruses can help to deepen insight into the pathogenesis of lymphoma, and identifying associations between lymphoma and viruses that are established and unidentified should lead to cellular and pharmacologically targeted antiviral strategies for treating malignant lymphoma. This review focuses on the pathogenesis of lymphomas associated with hepatitis B and C, Epstein-Barr, and human immunodeficiency viruses as well as Kaposi sarcoma-associated herpesvirus to clarify the current status of basic information and recent advances in the development of virus-associated lymphomas.